Predicting upper limb discomfort for plastic surgeons wearing loupes based on multi-objective optimization. Issue 1 (1st January 2017) - Li, Zhelin; Baber, Chris; Li, Francois-Xavier; Macdonald, Christopher; Godwin, Yvette
Abstract: Plastic surgeons report neck, shoulder and back pain when wearing head-mounted magnifiers (loupes) during operations. There will be many factors contributing to such pain. In order to explore these factors this paper developed a novel application of Multi-objective Optimization (MOO) which used postural constraints on anthropometric models to determine Rapid Upper Limb Analysis (RULA) scores. For the pain experienced by surgeons wearing loupes, the analyses showed that adjusting the height of table and suitable working distance of loupes for surgeon could decrease the flexion angle of neck. The results demonstrated that it is possible to predict RULA scores for the range of postures and propose that this approach could be used to quantify risk assessment, particularly in the selection and fitting of loupes and in the specification of working height for surgeons.